(S)Cars and the Great Recession. Issue 5 (14th October 2022) - Attanasio, Orazio; Larkin, Kieran; Ravn, Morten O.; Padula, Mario
Abstract : United States households' consumption expenditures and car purchases collapsed during the Great Recession and more so than income changes would have predicted. Using CEX data, we show that both the extensive and the intensive car spending margins contracted sharply in the Great Recession. We also document significant cross‐cohort differences in the impact of the Great Recession including a stronger reduction in car spending by younger cohorts. We draw inference on the sources of the Great Recession by investigating which shocks can explain household choices in a 60 period life‐cycle model with idiosyncratic and aggregate shocks fitted to aggregate and life‐cycle moments. We find that the Great Recession was caused by a combination of large aggregate income and wealth shocks, while cross‐cohort adjustment patterns imply a role for life‐cycle income profile shocks. We also find a role for car loan premia shocks in accounting for car spending and car loans.